Does better information drive better seed choices? Experimental evidence from Kenya - Ndegwa, Michael; Bulinda, Collins; Kariuki, Sarah Wairimu; Donovan, Jason; Rutsaert, Pieter; Jaleta, Moti (Elsevier, 2025)
Despite advances in hybrid maize performance in Kenya, many farmers continue planting varieties released over two decades ago. Farmer experimentation with and use of relatively newer hybrids is crucial to improve regional food security, especially amid the increasing pressures of climate change. This study uses a randomized controlled trial to assess the degree to which contextually relevant and product-specific performance information influences farmer seed choice. Farmers in the treatment group received yield data for ten hybrids grown by farmers in the previous growing season in their county, while those in the control group received placebo information unrelated to seed selection. The intervention tripled farmers' intent to buy top-performing hybrids (from 7% to 27%) and more than doubled actual purchases (from 5% to 13%). Stockouts prevented some intended purchases, but treated farmers were still more likely to choose these hybrids. This study highlights a critical gap: farmers tend to lack independent and credible up-todate information on seed performance. Investing in rigorous testing of currently available hybrids and improving how results are shared with farmers can help address this issue. Providing credible performance data can support better decision-making, speed up varietal turnover, and strengthen seed systems in Kenya and beyond.